Adaptive neuro-fuzzy controller for grid voltage dip compensations of grid connected dfig-wecs - Amin I.K.; Nasir Uddin M.; Hannan M.A.; Alam A.H.M.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Adaptive control systems; Asynchronous generators; Controllers; Electric current control; Electric drives; Electric fault currents; Electric power system control; Electric power transmission networks; Energy conversion; Fuzzy inference; Reactive power; Robust control; Two term control systems; Wind power; Adaptive network fuzzy inference systems; ANFIS; Conventional proportional integrals; Doubly fed induction generator (DFIG); Doubly fed induction generators; Neuro-fuzzy controller; Voltage dip; Wind energy conversion system; Electric machine control